Charis Christopher: capstone - Christopher, Charis, artist (Colorado State University. Libraries, 2017)
The artist's statement: Charis Christopher. Ephemeral Undulations at Tea Time. e·phem·er·al, /əˈfem(ə)rəl/, lasting for a very short time, synonyms: temporary, momentary, brief, fleeting, impermanent. un·du·late, /ˈənjəˌlāt/, move with a smooth wavelike motion, to rise and fall, surge, swell, heave, ripple, billow, flow, roll, etc., synonyms: curve, wind (snake-like), wobble, oscillate, fluctuate. Conscious vitality is an undulating dance of life and death. Balanced on a knife's edge, the two sided coin of our lives has every opportunity to wobble and weave between what is empirical and what is enigmatic. Harnessing my passion for metals I introspectively explore understanding the life I am given, my choices and actions and their resulting affects, and the inevitability of my death. A handmade mahogany-stained tea trolley sporting steel-rimmed wheels symbolizes gumption, determination, and understated style. These are personality traits of mine that support my ideals which are manifested in the metal works I create. I work in copper and silver with an emphasis on fabrication, riveting, raising, chasing and repoussé, chain making, and wearable art. Throughout history, copper has been thought to bring warmth and balance to its surrounding environment and silver is associated with the moon and stars, memory, purity and spirituality. When coupling the motherly strength, sturdiness, and assuredness of the warm, earth-centric copper with the bright, ethereal, silver it may bring balance and understanding of the two sides of existence: the experiential being and the mysterious otherness. Curling tendrils of steam symbolize an individual's choices and the outside influences that sculpt the path of one's life. Steam, smoke and rising vapors are visual reminders of the inevitability of death through the mere passage of time; sit watching a hot cup of tea long enough and the steam rising off it will disappear only remembered by the condensation left on the cup's walls. Spiraling whiffs of smoke and steam and death are natural. I believe endings should be acknowledged while still alive so that life may be enjoyed to the fullest. I plan to travel through this ephemeral life knowing this is all the time I am given to dance the most beautiful undulations I may choose for myself.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: metalsmithing